Current Trends in Surgical Airway Management of Neonates with Robin Sequence. Issue 11 (November 2018) - Fan, Kenneth L.; Mandelbaum, Max; Buro, Justin; Rokni, Alex; Rogers, Gary F.; Chao, Jerry W.; Oh, Albert K.
Abstract : Background: Robin sequence is defined by the clinical triad of micrognathia, glossoptosis, and upper airway obstruction, and is frequently associated with cleft palate and failure to thrive. Though the efficacy of certain surgical interventions to relieve airway obstruction has been well established, algorithms dictating decision making and perioperative protocols are poorly defined. Methods: A 22-question survey was sent via e-mail to members of the American Cleft Palate-Craniofacial Association and International Society of Craniofacial Surgeons. Questions were related to surgeon experience in treating neonates with Robin sequence, and specific perioperative protocols. Results: One hundred fifty-one responses were collected. Most respondents were surgeons practicing in North America(82.8%), in a university hospital setting (81.5%) and had completed a fellowship in pediatric plastic surgery or craniofacial surgery (76.2%). Preoperative protocols varied widely by years in training and location of practice. Although 78.8% of respondents always performed direct laryngoscopy, only 49.7% of respondents routinely obtained preoperative polysomnography. Mandibular distraction osteogenesis was the most common primary surgical airway intervention reported by 74.2%, with only 12.6% primarily utilizing tongue-lip adhesion. Slightly less than half of respondents ever performed tongue-lip adhesion. Operative selection was influenced by surgeon experience, with 80% of those in practice 0–5 years primarily utilizing mandibular distraction, compared with 56% of respondents in practice >15 years. Conclusions: This study documents wide variations in preoperative, operative, and postoperative protocols for the surgical airway management of neonates with severe Robin sequence. These results underscore the need to acquire more objective data, to compare different protocols and outcome measures.